Foundations of GTK+ Development - Krause, Andrew (Apress : Imprint: Apress, 2007)
GTK+ is one of the most influential graphical toolkits for the Linux operating system. It is the technology upon which the GNOME and XFCE desktop environments are based, and its crucial to have clear understanding of its complexities to build even a simple Linux desktop application. Foundations of GTK+ Development guides you through these complexities, laying the foundation that will allow you to cross from novice to professional. Foundations of GTK+ Development is aimed at C programmers and presents numerous real-life examples that you can immediately put to use in your projects. Some familiarity with C programming is assumed, as the book delves into new topics from the beginning. Topics like object inheritance are covered early on to allow for complete understanding of code examples later. And the provided examples are real-life situations that can help you get a head start on your own applications.